Analisis Pengaruh Falsafah al-Sufasta’iyyah dalam Filem Mentega Terbang Menurut Perspektif Falsafah Islam dan Ilmu Kalam: Analysis of the Influence of Sophism Philosophy in the Mentega Terbang Film According to the Perspective of Islamic Philosophy and Kalam - Saful Amin, Mohd Saiful Aqil Naim; Syed Abdul Rahman, Syed Mohammad Hilmi (Jurnal Usuluddin, 2023)
The philosophy of sophists is a thought that was started by a pre-Socratic philosopher named Protagoras (d. 420 BC). This thought became an epidemic of thought for the Greek civilization in understanding the concept of truth and the essence of thing. The sophists thought brought by Protagoras became the foundation stone for the philosophy of skepticism and also relativism thus urging the Greek philosophers to came up with science of logic to prove the reality. Nevertheless, this thought is still found in the past and present. On November 28, 2021, a controversial film titled Mentega Terbang was shown and it touched the sensitivity of Islam in particular. Therefore, this article was written to analyze and criticize the influence of that philosophy on this film through the method of literature review and data content analysis from the film from the perspective of islamic philospohy and knowledge of kalam. The results of the study found the elements and influence of sophists philosophy on this film despite with new variations and narrative. This indirectly proves the role of the knowledge of kalam in facing the doubts and threats of faith in today’s age.